Analisis Dampak Pandemi Covid-19 Terhadap Struktur Aktiva Dan Struktur Modal Pada Perusahaan BUMN Yang Terdaftar Di Bursa Efek Indonesia - Alfiani, Alfiani; Mulyati, Henny (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2022)
Analysis of the Impact of the Covid-19 Pandemic on Asset Structure and Capital Structure in State-Owned Enterprises Listed on the Indonesia Stock Exchange. The impact of the Covid-19 pandemic is very bad for the economy in Indonesia, especially in external factors. This study aims to examine the comparative analysis of the COVID-19 pandemic on the Asset Structure and Capital Structure of BUMN Companies Listed on the Indonesia Stock Exchange. The sample selection in this study used a purposive sampling method and it was found that 23 companies were in accordance with the criteria. The data of this study were obtained from the Indonesia Stock Exchange. The results of this study show that the performance of asset and capital structures in 2019 before the pandemic and in 2020 during the pandemic did not occur significantly. This research was conducted in a state-owned company.